Physical unclonable functions based on crossbar arrays for cryptographic applications. (28th June 2012) - Lugli, Paolo; Mahmoud, Ahmed; Csaba, György; Algasinger, Michael; Stutzmann, Martin; Rührmair, Ulrich; Csurgay, Árpád I.; Porod, Wolfgang
SUMMARY Due to their attractive, regular structure and their simple implementation, crossbar arrays have become one major emerging research area in the fields of nano‐devices and electronic circuits. This paper discusses novel applications of crossbars as various types of so‐called physical unclonable functions (PUFs) in the field of physical cryptography. The latter is a recent branch of cryptography and security that exploits the inherent, small‐scale randomness and disorder in physical structures. PUFs are the currently dominant primitive within this new field. In order to establish the applicability of crossbar structures as PUFs, two crossbars with rectifying junctions are investigated on the basis of real measurement data. In addition, the scalability of these crossbars with respect to their power dissipation and noise margin is evaluated in simulations. The types of PUFs as which crossbars can serve include weak PUFs and super high information content PUFs. We also discuss whether crossbar‐based PUFs allow the erasure and/or rewriting of response information on a single challenge‐response‐pair level, i.e. without affecting other PUF responses. Copyright © 2012 John Wiley & Sons, Ltd.